The Determinants and Outcomes of Host Government’s Motives and Policies for Inward Foreign Direct Investments - Toh, Terry Hong Weng (2014)
This study contributes to the area of Economics particularly in foreign direct investment (FDI) of an emerging market. It attempts to find out how emerging markets such as Malaysia could compete for inward FDIs. This study verified that MNEs in Malaysia used transaction cost theory for their entry mode. It also verified that, labour quality and infrastructure development were the most important determinants in services FDI as well as host governments could use the same policies to attract both manufacturing and services FDI. This study also found that the Malaysian government pursued policies in line with the recommendations made in researches on FDI but also carried out dualistic investment policies which favoured the country’s sociopolitical objectives at the expense of deteriorating its inward FDI. Unfortunately, this research could not verify whether the Malaysian government had done enough to attract FDI from China or India and linkages between foreign investment and locally-owned enterprises in Malaysia were found only in the business services industry.